Sun Protection Factor Activity of Black Glutinous Rice Emulgel Extract (Oryza sativa var glutinosa) - Farhamzah, Farhamzah; Kusumawati, Anggun Hari; Alkandahri, Maulana Yusuf; Hidayah, Himyatul; Sujana, Dani; Gunarti, Neni Sri; Yuniarsih, Nia; Apriana, Sukma Dewi; Agustina, Lilis Setianingsih (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Recently, emulgel has emerged as a potential hydrophobic drug delivery method. Therefore, this study aims to evaluate the phytochemical content of Oryza sativa extract and develop an emulgel formulation using Carbapol 940 as a gelling agent. Materials and Methods: The emulsion was placed in a gel basis after preparation and the formulations were evaluated for their rheology, pH, spreading coefficient, stability, and sun protection factor. Then, phytochemical analysis of O. sativa extract was used to determine the presence of alkaloids, flavonoids, polyphenols, quinones, monoterpenoids, and sesquiterpenoids, as well as triterpenoids and steroids. Results: The entire formulations of O. sativa emulgel extract filled the emulgel formulation criteria. Furthermore, O. sativa emulgel protects against UV radiation, as indicated by the SPF value in each formulation, which increases as the dose of O. sativa extract increases. Based on the results, formulations 2 and 3 have an SPF of 5.71±0.063 and 16.07±0.072, respectively. These suggest that they both fill the Indonesian National Standard, which requires a sunscreen preparation with a minimum of four protection. Conclusion: Consequently, O. sativa emulgel extract can serve as a novel sunscreen agent against UV radiation. However, further study is required to ascertain the mechanism of action of the active chemicals found in O. sativa that function as an antioxidant and give protection against UV radiation.
Keywords: Oryza sativa; Emulgel; Sun Protection Factor; Ultraviolet; Phytochemical; compounds